2018
DOI: 10.1371/journal.pone.0198285
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight heparin venous thromboprophylaxis in critically ill patients with renal dysfunction: A subgroup analysis of the PROTECT trial

Abstract: IntroductionThere is concern about excessive bleeding when low-molecular-weight heparins (LMWHs) are used for venous thromboembolism (VTE) prophylaxis in renal dysfunction. Our objective was to evaluate whether LMWH VTE prophylaxis was safe and effective in critically ill patients with renal dysfunction by conducting a subgroup analysis of PROTECT, a randomized blinded trial.MethodsWe studied intensive care unit (ICU) patients with pre-ICU dialysis-dependent end-stage renal disease (ESRD; pre-specified subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…Despite the increased bleeding risk with enoxaparin, there was no observed decrease in VTE. Our findings are unique as the majority of our patients experienced AKI, which is in contrast to the current literature that enrolled mostly patients with chronic renal disease 11‐13 . However, this makes our findings less generalizable to other types of renal impairment.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Despite the increased bleeding risk with enoxaparin, there was no observed decrease in VTE. Our findings are unique as the majority of our patients experienced AKI, which is in contrast to the current literature that enrolled mostly patients with chronic renal disease 11‐13 . However, this makes our findings less generalizable to other types of renal impairment.…”
Section: Discussioncontrasting
confidence: 68%
“…The study demonstrated less major bleeding with UFH post‐intervention with no difference in the rate of VTE. Conversely, a subgroup analysis of the PROTECT study compared the efficacy and safety of prophylactic LMWH versus UFH in patients with severe or end‐stage renal disease 12 . The subgroup analysis found no difference in major bleeding or thromboembolic events between UFH and LMWH.…”
Section: Introductionmentioning
confidence: 99%
“…When dalteparin 5000 IU daily was compared with UFH 5000 IU twice daily in patients with renal insufficiency or end-stage renal disease (ESRD), there was no significant difference in the incidence of VTE or major bleeding. Patients with severe renal dysfunction who were on dalteparin did have a greater incidence of proximal DVTs compared to those on UFH; there was no greater risk of VTE or major bleeding [ 40 ].…”
Section: Reviewmentioning
confidence: 99%
“…For patients with high risk of bleeding, graduated compression stockings (GCS) and (or) intermittent pneumatic compression (IPC) were used to prevent thrombosis until the risk of bleeding was reduced, and then chemoprophylaxis should be prescribed or both were used in combination. ICU patients should be evaluated dynamically according to the development of the disease (26). García-Olivares and other researchers discovered that establishing a prophylaxis protocol in the ICU can reduce the incidence of VTE from 11.9% to 4.5% (27,28).…”
Section: Comparing Prophylaxis In High Vte Risk Patients With Bleeding Risk Among Elderly Icu Patientsmentioning
confidence: 99%